Validity of the jump test for assessing the anaerobic perfomance and asymmetry in elite cyclists - Muriel Otegui, Xavier; Cámara Tobalina, Jesús; Fernández López, Juan Ramón; Pallarés, Jesús G. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2012)
This study aimed to validate the countermovement jump test (CMJ) to estimate the anaerobic performance, as well as to study the asymmetry in the power application between left and right legs in elite cyclists. All participants performed a 30s Wingate test (WAnT) on a cycle ergometer and a CMJ test with force and power records on each leg. The results indicate that the CMJ flight time correlated significantly (r=.61-.80, P<.05) with the mechanical efficiency as well as with the average and maximum WAnT power. However, the asymmetry between legs recorded in both test (CMJ vs. WAnT) did not significantly correlate. These results suggest that the CMJ can be a valid test to estimate the anaerobic metabolism performance in elite cyclists, although there seems not to be a valid test for detecting strength deficits in the forces applied between legs.